Landslides from Massive Rock Slope Failure - Evans, Stephen G.; Mugnozza, Gabriele Scarascia; Strom, Alexander; Hermanns, Reginald L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Amongst the thematic topics discussed are global frequency, impacts on society, analysis of initial rock slope failure, monitoring of rock slope movement, analysis and modeling of post-failure behaviour, volcanic landslides, and influences of massive rock slope failure on the geomorphological evolution of mountain regions. Regional contributions include reports on rockslides and rock avalanches in Norway, western Canada, the Andes of Argentina, the Karakoram Himalaya, the European Alps, the Appennines, and the mountains of Central Asia. Rockslides and rock avalanches in the Central Asian republics of the former Soviet Union are discussed in detail for the first time in an English-language book. These landslides include the 1911 Usoi rockslide, that dammed 75 km-long Lake Sarez, and the 1949 Khait rock avalanche that may have killed up to 28,000 people. Both landslides were earthquake-triggered and both are located in Tajikistan. An additional highlight is a detailed description and analysis of large-scale artificial rock avalanches triggered by underground nuclear explosions during the testing programme of the former Soviet Union.
LANDSLIDES FROM MASSIVE ROCK SLOPE FAILURE AND ASSOCIATED PHENOMENA -- SINGLE-EVENT LANDSLIDES RESULTING FROM MASSIVE ROCK SLOPE FAILURE: CHARACTERISING THEIR FREQUENCY AND IMPACT ON SOCIETY -- ANALYSIS OF INITIAL ROCK SLOPE FAILURE -- ON THE INITIATION OF LARGE ROCKSLIDES: PERSPECTIVES FROM A NEW ANALYSIS OF THE VAIONT MOVEMENT RECORD -- FROM CAUSE TO EFFECT: USING NUMERICAL MODELLING TO UNDERSTAND ROCK SLOPE INSTABILITY MECHANISMS -- GRAVITATIONAL CREEP OF ROCK SLOPES AS PRE-COLLAPSE DEFORMATION AND SOME PROBLEMS IN ITS MODELLING -- MODELS AVAILABLE TO UNDERSTAND FAILURE AND PRE-FAILURE BEHAVIOUR OF LARGE ROCK SLOPE MOVEMENTS: THE CASE OF LA CLAPIÈRE, SOUTHERN ALPS, FRANCE -- NUMERICAL MODELLING OF ROCK SLOPES USING A TOTAL SLOPE FAILURE APPROACH -- THE ROLE OF TOPOGRAPHIC AMPLIFICATION ON THE INITIATION OF ROCK SLOPES FAILURES DURING EARTHQUAKES -- MONITORING OF ROCK SLOPE MOVEMENT -- APPLICATION OF GROUND-BASED RADAR INTERFEROMETRY TO MONITOR AN ACTIVE ROCKSLIDE AND IMPLICATIONS FOR EMERGENCY MANAGEMENT -- MONITORING AND ASSESSING THE STATE OF ACTIVITY OF SLOPE INSTABILITIES BY THE PERMANENT SCATTERERS TECHNIQUE -- ANALYSIS OF POST-FAILURE BEHAVIOUR -- FORECASTING RUNOUT OF ROCK AND DEBRIS AVALANCHES -- CONTINUUM NUMERICAL MODELLING OF FLOW-LIKE LANDSLIDES -- ANALYSIS OF POST-FAILURE BEHAVIOUR -- ROCK AVALANCHE OCCURRENCE, PROCESS AND MODELLING -- MOBILITY OF ROCK AVALANCHES TRIGGERED BY UNDERGROUND NUCLEAR EXPLOSIONS -- INFERENCES FROM THE MORPHOLOGY AND INTERNAL STRUCTURE OF ROCKSLIDES AND ROCK AVALANCHES RAPID ROCK MASS FLOW WITH DYNAMIC FRAGMENTATION: -- MORPHOLOGY AND INTERNAL STRUCTURE OF ROCKSLIDES AND ROCK AVALANCHES: GROUNDS AND CONSTRAINTS FOR THEIR MODELLING -- CASE STUDIES OF MASSIVE ROCK SLOPE FAILURE -- THE FLIMS ROCKSLIDE: HISTORY OF INTERPRETATION AND NEW INSIGHTS -- ROCK AVALANCHE AND MOUNTAIN SLOPE DEFORMATION IN A CONVEX DIP-SLOPE: THE CASE OF THE MAIELLA MASSIF, CENTRAL ITALY -- SLOW-MOVING DISINTEGRATING ROCKSLIDES ON MOUNTAIN SLOPES -- EDOARDO SEMENZA: THE IMPORTANCE OF GEOLOGICAL AND GEOMORPHOLOGICAL FACTORS IN THE IDENTIFICATION OF THE ANCIENT VAIONT LANDSLIDE -- FAILURE MECHANISMS AND RUNOUT BEHAVIOUR OF THREE ROCK AVALANCHES IN THE NORTH-EASTERN ITALIAN ALPS -- VOLCANIC LANDSLIDES -- LARGE MODERN COLLAPSES ON THE ACTIVE VOLCANOES OF KAMCHATKA: CAUSES AND MECHANISM OF FORMATION -- ASSESSING MASSIVE FLANK COLLAPSE AT STRATOVOLCANOES USING 3-D SLOPE STABILITY ANALYSIS -- CATASTROPHIC VOLCANIC LANDSLIDES: THE LA OROTAVA EVENTS ON TENERIFE, CANARY ISLANDS -- REGIONAL STUDIES OF MASSIVE ROCK SLOPE FAILURE -- ROCK SLOPE FAILURES IN NORWEGIAN FJORD AREAS: EXAMPLES, SPATIAL DISTRIBUTION AND TEMPORAL PATTERN -- OF COMPLEX INTERACTIONS OF LITHOLOGIC, STRUCTURAL AND TOPOGRAPHIC BOUNDARY CONDITIONS, CLIMATE CHANGE AND ACTIVE TECTONICS ROCK AVALANCHING IN THE NW ARGENTINE ANDES AS A RESULT -- ROCK AVALANCHES WITH COMPLEX RUN OUT AND EMPLACEMENT, KARAKORAM HIMALAYA, INNER ASIA -- DISSECTED ROCKSLIDE AND ROCK AVALANCHE DEPOSITS; TIEN SHAN, KYRGYZSTAN -- INFLUENCES ON GEOMORPHOLOGICAL EVOLUTION -- LANDSLIDE-DRIVEN EROSION AND TOPOGRAPHIC EVOLUTION OF ACTIVE MOUNTAIN BELTS -- IMPACTS OF LANDSLIDE DAMS ON MOUNTAIN VALLEY MORPHOLOGY -- STATE-OF-THE-ART -- MASSIVE ROCK SLOPE FAILURE : PERSPECTIVES AND RETROSPECTIVES ON STATE-OF-THE-ART.
Keywords: Earth sciences; Geotechnical engineering; Physical geography; Environment; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Physical Geography; Environment, general; Electronic books